ANALYSIS OF VISITORS' PERCEPTIONS OF THE QUALITY OF JUNGLE TRACKING TOURISM: A CASE STUDY OF SUMBER AGUNG VILLAGE - Heyrica Karendewe; Gunardi Djoko Winarno; Trio Santoso; Dian Iswandaru (Universitas Nusa Bangsa, 2026)
Nature-based tourism continues to grow as a popular tourism activity among the public. Effective destination management must prioritize destination quality to provide an optimal visitor experience. This study aimed to analyze visitors’ perceptions of the quality of the Jungle Tracking nature tourism destination in Sumber Agung Village. Perceptions were assessed based on five aspects: tourist attractions, infrastructure, facilities and services, accommodation, and organization and human resources. This study used a survey method with questionnaires distributed to 68 visitors participating in Jungle Tracking activities during the research period. Most respondents were dominated by young visitors aged 17–25 years. Data were analyzed descriptively using a Likert scale. The results showed that visitors’ perceptions of the quality of the Jungle Tracking destination were generally in the “fairly good” to “good” categories. The tourist attraction aspect received the highest assessment due to the natural scenery and environmental conditions of the area. Meanwhile, infrastructure and tourism facilities were considered adequate, although several components still need improvement, particularly directional signs, tourist information, and management coordination. Improving facilities and destination management is necessary to support sustainable nature tourism development in Sumber Agung Village.